Aus der Geschichte der Deutschen Gesellschaft für Innere Medizin (DGIM) - Forsbach, Ralf; Hofer, Hans-Georg (DMW - Deutsche Medizinische Wochenschrift, 2018)
Although times were difficult in 1947/48 – with war damage, travel restrictions and the East-West conflict – the German Society for Internal Medicine not only managed to re-organise itself but also hosted its first scientific congress in that year. The DGIM members Franz Volhard and Paul Martini, who rather disapproved of the Nazi regime, played a decisive role in this process. However, a critical discussion of the NS medical crimes, which occurred just a few years ago, remained the exception. It is interesting to note that members who were persecuted by the NS regime were nevertheless willing to attend a congress that obviously provided a forum for the protagonists of the Nazi era.This work presents – for the first time – an overview of the specific conditions of the reconstitution of the German Society for Internal Medicine and enriches our knowledge about the actions of the medical societies in the years between the fall of the Nazi regime and the founding of the two German states.
Keywords: Medizingeschichte; Deutsche Gesellschaft für Innere Medizin; Nachkriegszeit; Paul Martini; Franz Volhard